PERANAN BAHAN ORGANIK Chromolaena odorata DAN Crotalaria juncea DALAM MENINGKATKAN KETERSEDIAAN HARA FOSFOR BAGI PERTUMBUHAN TANAMAN KEDELAI DI LAHAN KERING - St.Subaedah St.Subaedah (Percetakan Umi Toaha Makassar, 2017)
The development of soybean crops in dry land are often confronted with low soil fertility which causes be hampered growth and crop production. The efforts to manage soil fertility with application of fertilizer chemical also did not have much effect, because the soil buffering capacity is low which causes the fertilizer is given can be leached out or bound by other elements (especially elements P), so that P can not be absorbed by plants, while P is an element plants need in large quantities. This study aims to improve the availability of nutrients phosphate for renewed growth in soybean crops in dry land. This study aims to improve the availability of nutrients phosphate for renewed growth in soybean crops in dry land. This study was designed with a completely randomized design, factorial of two factors. The first factor is the kind of organic material consisting of four levels ie: without any organic material, organic material from plants Chromolaena odorata, organic material from plants Crotalaria juncea and organic matter from manure. The second factor is P fertilization that consists of two levels, namely: 50 kg-36.ha SP-1 and SP-36.ha 100 kg-1. The results showed that the organic matter C. odorata and C. juncea with P fertilization can improve nutrient availability in the soil P, P nutrient uptake by soybean plants also increased with organic matter C. odorata and C. juncea accompanied fertilization P.